Distribuição de competências à luz da ADI 6.343 - Oliveira, Gustavo de [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
This paper addresses the understanding of the Supreme Federal Court regarding the constitutional competencies of the federal entities in the context of the COVID-19 pandemic, analyzed from the Direct Action of Unconstitutionality 6.343. In this regard, the scope of investigation of this work falls within the theme of federalism, studied based on its practical and theoretical manifestations, highlighting the distinction between its dualistic and cooperative aspects. The general objective of the work is to present the reasons that led the Justices to the final result of the decision, as well as an analysis of these same reasons and related issues made from premises derived, essentially, from the Constitutional Law. To this end, the court's reasoning is presented as a basis for the respective analysis, also considering the votes that were not victorious in the trial. The conclusions reached show that the court advocated the decentralization criterion when interpreting federalism in Brazil, understanding, by majority vote, for the application of common and concurrent competencies in the case to the detriment of the Union's exclusive competence for planning and promoting permanent defense against public calamities.

O presente trabalho aborda o entendimento do Supremo Tribunal Federal a respeito das competências constitucionais dos entes federados no contexto da pandemia do COVID-19, analisado a partir da Ação Direta de Inconstitucionalidade 6.343. Nesse sentido, o campo de investigação do trabalho se insere na temática do federalismo, estudado com base nas suas manifestações práticas e teóricas, destacando-se a distinção entre suas vertentes dualista e cooperativa. Como objetivo geral do trabalho, visa-se apresentar a fundamentação que levou os Ministros julgadores ao resultado final da decisão, assim como uma análise desses mesmos fundamentos e questões conexas feita a partir de premissas oriundas, essencialmente, do Direito Constitucional. Para isso, apresenta-se o que motivou a decisão do tribunal para fins de embasar a respectiva análise, considerando-se, também, os votos que não foram vitoriosos no julgamento. As conclusões alcançadas mostram que a corte preconizou o critério da descentralização ao interpretar o federalismo no Brasil, entendendo, por maioria de votos, pela aplicação das competências comuns e concorrentes no caso em detrimento da competência exclusiva da União para o planejamento e promoção da defesa permanente contra as calamidades públicas.
Distribution of competencies in light of ADI 6.343
Keywords: Federalism; Competencies; Pandemic; Constitution; Federalismo; Competências; Pandemia; Constituição